A systematic review on risk factors for reduced lung function due to occupational respirable dust exposures; 2005 - 2015 - Masngut, Mohd Izwan; Baharudin, Mohd Rafee; Abdul Rahman, Anita (Community Health Society Malaysia, 2015)
Background: Occupational exposures to respirable dust includes various hazardous substances were commonly associated with acute and chronic health effects especially on respiratory system and lung function performance among workers in various industries.